Word up – Experiential and neurocognitive evidence for associations between autistic symptomology and a preference for thinking in the form of words. (July 2020) - Turnbull, Adam; Garfinkel, Sarah N.; Ho, Nerissa S.P.; Critchley, Hugo D.; Bernhardt, Boris C.; Jefferies, Elizabeth; Smallwood, Jonathan
Abstract: Autism symptomology has a profound impact on cognitive and affective functioning, yet we know relatively little about how it shapes patterns of ongoing thought. In an exploratory study in a large population of neurotypical individuals, we used experience sampling to characterise the relationship between ongoing cognition and self-reported autistic traits. We found that with increasing autistic symptom score, cognition was characterised by thinking more in words than images. Analysis of structural neuroimaging data found that autistic traits linked to social interaction were associated with greater cortical thickness in a region of lingual gyrus (LG) within the occipital cortex. Analysis of resting state functional neuroimaging data found autistic traits were associated with stronger connectivity between the LG and a region of motor cortex. Importantly, the strength of connectivity between the LG and motor cortex moderated the link between autistic symptoms and thinking in words: individuals showing higher connectivity showed a stronger association between autistic traits and thinking in words. Together we provide behavioural and neural evidence linking autistic traits to the tendency to think in words which may be rooted in underlying cortical organisation. These observations lay the groundwork for research into the form and content of self-generated thoughts in individuals with the established diagnosis of autism.